Implementasi Pengembangan Agribisnis di Kabupaten Tasikmalaya - Ade Iskandar (Universitas Bandar Lampung (UBL), 2015)
Implementation of Agricultural Development in Tasikmalaya District implemented by Regional Regulation No. 13 Year 2011 on Medium Term Development Plan Tasikmalaya Regency Year 2011-2015 which brings consequences on the implementation of one of its mission Tough Economy Brought to the Rural-Based Agribusiness Excellence. In terms of implementation of agribusiness development in Tasikmalaya district requires the existence of some things as proposed Jones (1996: 105), among others Organization; Interpretation; and Application. Organizational structuring begins with basic tasks and functions of each relevant agencies, structuring the management of natural resources, human resources and other resources, including facilities and infrastructure. Interpretation of the policies of agribusiness development in Tasikmalaya regency which translated into a plan and direction. Policy agribusiness development in Tasikmalaya district is translated into strategic plans of each regional organization concerned. Application of agribusiness development policies carried out by structuring a more quality service provision.